The ZIPA moment: Dzino, Mugabe and Samora Machel. (22nd August 2016) - Saul, John S.
ABSTRACT: This article underscores the importance of the relatively brief life but historically noteworthy emergence of the Zimbabwe People's Army (ZIPA) within the struggle for Zimbabwean liberation in the 1970s. For ZIPA was a movement that offered both a serious military challenge of its own to Smith's UDI regime but also the long-term possibility of a far more meaningful liberation than anything achieved since by ZANU's 'old guard' under the orchestration of Robert Mugabe. The roles played by Mugabe, Machel, Kaunda, Kissinger and Crosland in ensuring ZIPA's defeat are all emphasised, with a key source for the paper's reinterrogation of ZIPA's role being the recent autobiography of Wilfred Mhanda (aka Dzino Machingura), entitled Dzino . A link is also made to Lionel Cliffe's writing of the time (in ROAPE issue no. 8), in particular to his own experience while incarcerated in one of Kaunda's Zambian jails.